Glucose restriction combined with autophagy inhibition and chemotherapy in HCT 116 spheroids decreases cell clonogenicity and viability regulated by tumor suppressor genes - Schroll, Monica M. (J Proteome Res, 2017)
Drug resistance is a prevalent phenomenon that decreases the efficacy of cancer treatments and contributes to cancer progression and metastasis. Weakening drug resistant cancer cells prior to chemotherapy is a potential strategy to combat chemoresistance. One approach to damage resistant cancer cells is modulation of nutritional intake. The combination of nutrient restriction with targeted compound treatment results in pronounced molecular changes. This study provides valuable information about augmenting existing chemotherapeutic regimes with simultaneous glucose restriction and autophagy inhibition in colorectal cancer cells. In this study, we explore the chemical pathways that drive the cellular response to nutrient restriction, autophagy inhibition and the chemotherapy irinotecan using global quantitative proteomics and imaging mass spectrometry. We determined that significant pathways were altered including autophagy and metabolism via glycolysis, gluconeogenesis, and sucrose degradation. We also found that period circadian clock 2 (PER2), a tumor suppressor protein, was significantly up regulated only when glucose was restricted with autophagy inhibition and chemotherapy. The upstream regulators of these differentially regulated pathways were determined to have implications in cancer, showing an increase of tumor suppressor proteins and a decrease in nuclear protein 1 (NUPR1) an important protein in chemoresistance. We also evaluated the phenotypic response of these cells and discovered autophagy inhibition and chemotherapy treatment increased apoptosis and decreased cell clonogenicity and viability. When glucose restriction was combined with autophagy inhibition and chemotherapy, all of the phenotypic results were intensified. In sum, our results indicate that glucose metabolism is of great importance in the ability of cancer cells to survive chemotherapy. By weakening cancer cells with glucose restriction and autophagy inhibition prior to chemotherapy, cancer cells become more sensitive to therapy.